Prezi

Present Remotely

Send the link below via email or IM

Copy

Present to your audience

Start remote presentation

  • Invited audience members will follow you as you navigate and present
  • People invited to a presentation do not need a Prezi account
  • This link expires 10 minutes after you close the presentation
  • A maximum of 30 users can follow your presentation
  • Learn more about this feature in the manual

Do you really want to delete this prezi?

Neither you, nor the coeditors you shared it with will be able to recover it again.

DeleteCancel

Make your likes visible on Facebook?

Connect your Facebook account to Prezi and let your likes appear on your timeline.
You can change this under Settings & Account at any time.

No, thanks

OPERACIONES CON FUNCIONES Y FUNCION COMPUESTA

No description
by Clara Perez on 7 December 2012

Comments (0)

Please log in to add your comment.

Report abuse

Transcript of OPERACIONES CON FUNCIONES Y FUNCION COMPUESTA

Dadas las funciones f y g se define la función compuesta:

Se calcula: poniendo en la expresión de g, en lugar de x, la expresión de f(x).
El símbolo (o) entre las funciones indica la operación función y el resultado es una nueva función que también dependerá de x.
La Composición entre funciones NO ES UNA OPERACIÓN CONMUTATIVA Por: Clara Edith Pérez
Carolina Naranjo OPERACIONES CON FUNCIONES Y FUNCIÓN COMPUESTA SUMA RESTA MULTIPLICACIÓN FUNCIÓN COMPUESTA DIVISIÓN Dadas dos funciones f(x) y g(x) se define la función suma f +g por:


Ej: Sea f(x) = x+3 y g(x)= x^2 + 2x – 4.
(f +g)(x) = f(x)+g(x)
= x+3 + x^2 + 2x – 4
= x^2 + 3x – 1. Dadas dos funciones f(x) y g(x) se define la
función resta f-g por:


Ej: Sea f(x) = x^2-5x+2 y g(x)=2x^2+x-4
(f-g)(x)=f(x)-g(x)
=(x^2-5x+2)-(2x^2+x-4)
= x^2-5x+2-2x^2-x+4
= (-x)^2-6x+6 Dadas dos funciones f y g se define la función
producto f.g así:


Ej: Sea f(x) = x+3 y g(x)= x^2+2x–4
(f.g)(x) = f(x).g(x)
= (x+3).(x^2+2x–4)
= x^3+2x^2–4x+3x^2+6x-12
= x^3+5x^2+2x-12 Dadas dos funciones f y g se define la función cociente f/g por:




Ej: Sea f(x) = x+3 y g(x)= x^2+2x–4.
(f/g)(x) =f(x)/g(x)
= (x+3)/(x^2+2x–4) Dadas las funciones:
f(x)= x +3
Calcula:
g o f = g(f(x))
= (f(x))^2
= (x+3)^2
= x^2+6x+9 (f +g)(x)=f(x)+g(x) (f +g)(x)=f(x)+g(x) f.g)(x)= f(x).g(x) (f/g)(x) = f(x)/g(x), g(x) ≠ 0 ok f compuesta con g : g o f(x) = g(f(x)) f [g(x)] ≠ g[f (x)] f o g = f(g(x)) g(x)= x^2 = g(x)+3
= x^2+3 GRACIAS POR
SU ATENCIÓN
See the full transcript